2005
DOI: 10.1128/aem.71.8.4307-4317.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacteria on Artemia franciscana Cultured in Different Gnotobiotic Environments

Abstract: The use of probiotics is receiving considerable attention as an alternative approach to control microbiota in aquaculture farms, especially in hatching facilities. However, application with consistent results is hampered by insufficient information on their modes of action. To investigate whether dead bacteria (allowing investigation of their nutritional effect) or live bacteria (allowing evaluation of their probiotic effect) have any beneficial effect towards Artemia franciscana and, subsequently, if live bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 43 publications
4
69
0
1
Order By: Relevance
“…Unclear allocation of sequence data at species level led to the formation of groups # 1 to # 4. Some authors reported similar findings of different bacterial species (Ivanova et al 2003 for Shewanella species; Marques et al 2005;Venkateswaran et al 1998 for Vibrio species; Mc Aucliffe et al 2003 for Mycoplasma species). The application of larger 16S rDNA or 23S rDNA fragments might be more appropriate in future experiments.…”
Section: Discussionsupporting
confidence: 59%
“…Unclear allocation of sequence data at species level led to the formation of groups # 1 to # 4. Some authors reported similar findings of different bacterial species (Ivanova et al 2003 for Shewanella species; Marques et al 2005;Venkateswaran et al 1998 for Vibrio species; Mc Aucliffe et al 2003 for Mycoplasma species). The application of larger 16S rDNA or 23S rDNA fragments might be more appropriate in future experiments.…”
Section: Discussionsupporting
confidence: 59%
“…After identification of disease-associated strains, the next major task was to evaluate the virulence potential of each strain. Artemia is an excellent model to study the mode of action of probiotics and pathogenic bacteria under gnotobiotic conditions (Marques et al, 2005). Austin et al (2005) evaluated the pathogenic potential of several vibrios using rainbow trout and Artemia as test organisms.…”
Section: Discussionmentioning
confidence: 99%
“…After 48 h, the numbers of live Artemia nauplii in each tube were counted and the mean percentage mortality (M obs ) with standard deviation (SD) was calculated. Nauplii were not fed throughout the experimental period to keep the experimental set-up contamination free as described by Marques et al (2005). Generally Artemia can survive in a healthy condition for up to 72 h without feeding (OrozcoMedina et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…As the susceptibility of Artemia to pathogenic V. campbellii depends on the quality of feed fed [27], a test was performed by feeding induced and non-induced bacterial strains to Artemia in order to examine their nutritional value. Artemia nauplii fed with E. coli had significantly (P < 0.05) higher survival and length compared with the non-fed Artemia (Table 4).…”
Section: Nutritional Effect Of the Bacterial Strainsmentioning
confidence: 99%